Protective effects of various ratios of DHA/EPA supplementation on high-fat diet-induced liver damage in mice - Tingting Shang; Liang Liu; Jia Zhou; Mingzhen Zhang; Qinling Hu; Min Fang; Yongning Wu; Ping Yao; Zhiyong Gong (Lipids in Health and Disease, 2017)
Abstract Background A sedentary lifestyle and poor diet are risk factors for the progression of non-alcoholic fatty liver disease. However, the pathogenesis of hepatic lipid accumulation is not completely understood. Therefore, the present study explored the effects of dietary supplementation of various ratios of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) on a high-fat diet-induced lipid metabolism disorder and the concurrent liver damage. Methods Using high-fat diet-fed C57BL/6 J mice as the animal model, diets of various ratios of DHA/EPA (2:1, 1:1, and 1:2) with an n-6/n-3 ratio of 4:1 were prepared using fish and algae oils enriched in DHA and/or EPA and sunflower seed oils to a small extent instead of the high-fat diet. Results Significantly decreased hepatic lipid deposition, body weight, serum lipid profile, inflammatory reactions, lipid peroxidation, and expression of adipogenesis-related proteins and inflammatory factors were observed for mice that were on a diet supplemented with DHA/EPA compared to those in the high-fat control group. The DHA/EPA 1:2 group showed lower serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein-cholesterol levels, lower SREBP-1C, FAS, and ACC-1 relative mRNA expression, and higher Fra1 mRNA expression, with higher relative mRNA expression of enzymes such as AMPK, PPARα, and HSL observed in the DHA/EPA 1:1 group. Lower liver TC and TG levels and higher superoxide dismutase levels were found in the DHA/EPA 2:1 group. Nonetheless, no other notable effects were observed on the biomarkers mentioned above in the groups treated with DHA/EPA compared with the DHA group. Conclusions The results showed that supplementation with a lower DHA/EPA ratio seems to be more effective at alleviating high-fat diet-induced liver damage in mice, and a DHA/EPA ratio of 1:2 mitigated inflammatory risk factors. These effects of n-3 polyunsaturated fatty acids (PUFA) on lipid metabolism may be linked to the upregulation of Fra1 and attenuated activity of c-Jun and c-Fos, thus ultimately reducing the severity of the lipid metabolism disorder and liver damage to some extent.